Propuesta de Ruta Turística de la parroquia Machachi, cantón Mejía provincia de Pichincha. - Coronel Yugsi, Katherine Johanna (2022)
The current research named TOURIST ROUTE PROPOSAL FROM THE MACHACHI PARISH, CANTON MEJÍA, PICHINCHA PROVINCE, has a qualitative approach with an exploratory scope. For the execution this research work was proposed three aims, such as: first aim, it was performed a Situational Diagnosis from Machachi parish, through the information compilation got in the Mejía canton PDOT, official pages and research related to the parish, what was the study object, as well as, was performed six field trips, sixty-nine surveys, which were made under the non-probabilistic method for convenience and three interviews to tourists, who visit Machachi, whom could be got more information about tourist demand. For the second aim fulfillment, it was developed a tourist attractions inventory from Machachi, through the cards use for the information collection and tourist attractions hierarchy created by MINTUR, for the cards development, it was carried out field trips, where it can collect information about the eighteen tourist attractions, subsequently, it was systematized the got information from each attraction into tables of summary, further, it was research the attractions from Machachi parish, bibliographically, in order to acquire more updated data each attractive. At the end, in order to achieve the third proposed aim, it was proposed to the technical elaboration from Tourist Route, which was named MACHACHI ROUTE, PARKS AND HISTORY, what was elaborated with the cultural tourist attractions inventoried into Machachi parish, in order to diversify the tourist, offer in the parish and strengthen the community economic processes and its inhabitants. For the route development was taken into account the Route Generation Manual provided by the Tourism Ministry and the SENA Tourist Routes Design.